KARAKTERISTIK PEMBAKARAN PADA MESO SCALE COMBUSTOR DENGAN BAHAN BAKAR BUTAN DAN LIQUEFIED PETROLEUM GAS - Ivan Bagus Sanjaya; Nasrul Ilminnafik; FX. Kristianta (ROTOR, 2017)
Increasing energy consumption causes problems of natural resources, especially fossil energy. Micro Power Generator (MPG) is a technological breakthrough that can help save fossil energy. There are two main parts to MPG, namely micro or meso scale combustor and a converter module. For optimizing meso scale combustor, the best fuel is needed between LPG and Butane. This research was conducted to determine the combustion characteristics of meso combustor at the equivalent variation ratio of 1.15 and 1.20 at the reactant rate of 30 cm / s. The study was conducted on ignition of the combustor meso scale space with dimensions of 30 ml in length and 3.5 ml in diameter, with variations in the supply of air in fixed fuel supply. Combustion characteristics include temperature and color of fire. Butane flame temperature in the variety of equivalent ratio is higher than that of LPG fire. The fire color produced by Butana is dark blue and light blue LPG. This shows that the combustion of butane in meso combustor is better than LPG. Keyword: Butane, LPG, combustor meso scale, fire color, flame temperature